BUDGET REPORT ANALYSIS AND BUDGET REALIZATION REFOCUSING COVID-19 - Anisa' Wildah Fajariah; Deni Juliasari; Noviansyah Rizal (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2021)
This study aims to analyze the Covid-19 Refocusing Budget and the Lumajang District Health Office Budget Realization Report according to the Joint Decree of the Minister of Home Affairs Number 119/2813/SJ and the Minister of Finance Number 177/KMK. 07/2020 as well as knowing the level of effectiveness and efficiency of the Covid-19 Refocusing Budget Realization. The results of the analysis are ineffective because local revenue at the Lumajang District Health Office has greatly decreased due to the Covid-19 pandemic, so the Regional Sports Health Center (BKOR) has to reduce the number of visitors and even temporarily close to suppress the spread of the corona virus in Lumajang Regency. And the expenditure realization is said to be quite effective because the realization percentage is 81.89%.